GIVING STUDENTS A BRIEF EXPLANATION OF ALTERNATIVE ENERGY SOURCES (Universal International Scientific Journal, 2026)
The article discusses the importance of alternative energy sources - solar, wind, hydropower, geothermal energy and biomass energy, their mechanisms of operation, and their environmental and economic advantages. It also analyzes state policy aimed at developing renewable energy sources in Uzbekistan.
Keywords: alternative energy, renewable energy, solar energy, wind energy, hydropower, biomass